POTENSI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN BANDOTAN (AGERATUM CONYZOIDES L) TERHADAP BAKTERI STAPHYLOCOCCUS EPIDERMIDIS DAN ESCHERICIA COLI: POTENSI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN BANDOTAN (AGERATUM CONYZOIDES L) TERHADAP BAKTERI STAPHYLOCOCCUS EPIDERMIDIS DAN ESCHERICIA COLI - Nur Aini Khairunnisa; Amanda Rahayu, Nurul; Husein, Saddam; Maulana Harahap, Armansyah; Pangondian, Aswan; Athaillah (FORTE JOURNAL, 2025)
Bandotan (Ageratum conyzoides L.) is a herbaceous plants that belonging to Asteraceae family which contained a diverse range of secondary metabolites including alkaloids, flavonoids, tannins, glycosides, and saponins. The diversity of its bioactive compounds confers Bandotan as natural ingredient with considerable pharmacological potential, particularly as an antioxidant, antibacterial, and insecticidal agent. The present study aimed to evaluate the antibacterial potential of the Ethanolic Extract of Ageratum conyzoides (EEAC)  Leaves against Staphylococcus epidermidis and Escherichia coli. Diffusion methode using in this study with various concentration from 31.25 until 500 ppm. The results showed that the Minimum Inhibitory Concentration (MIC) for both bacteria was at 31.25 ppm and the inhibition zone was at 10.3 for E. coli and 12.4 for S. epidermidis with 500 ppm concentration. In Minimum Bactericidal Concentration (MBC) test, it is known that EEAC has the highest potential to eradicate E. coli and S. epidermidis. According to this, EEAC has the strong potential effect againts both bacterial strains.